2017
DOI: 10.1093/cid/cix075
|View full text |Cite
|
Sign up to set email alerts
|

PERCH in Perspective: What Can It Teach Us About Pneumonia Etiology in Children?

Abstract: The pneumonia team at the Bill & Melinda Gates Foundation congratulates the Pneumonia Etiology Research for Child Health (PERCH) study on delivering on their grant to collect high-quality data from thousands of children with World Health Organization–defined severe and very severe pneumonia and from controls in 9 diverse sites in 7 low- and middle-income countries. This supplement sets the foundation to understanding this complex study by providing an in-depth description of the study methodology, including di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The lack of robust evidence on pneumonia aetiology in this age group means that best practice with regard to antibiotic treatment really is unknown. The recently completed Pneumonia Aetiology Research for Child Health study sought to refresh understanding of paediatric pneumonia aetiology in LMICs, but focused exclusively on under 5s 43. Unfortunately, we were unable to confirm aetiology in our study due to the limited diagnostic capacity of the study hospitals 8.…”
Section: Discussionmentioning
confidence: 91%
“…The lack of robust evidence on pneumonia aetiology in this age group means that best practice with regard to antibiotic treatment really is unknown. The recently completed Pneumonia Aetiology Research for Child Health study sought to refresh understanding of paediatric pneumonia aetiology in LMICs, but focused exclusively on under 5s 43. Unfortunately, we were unable to confirm aetiology in our study due to the limited diagnostic capacity of the study hospitals 8.…”
Section: Discussionmentioning
confidence: 91%
“…The large studies of the viral etiology of pneumonia conducted in recent years [24] , [25] , [33] , [34] represent a major leap forward in our knowledge of what causes lower respiratory tract disease. In these studies influenza has been consistently detected in a substantial proportion of pneumonia cases, but estimates of incidence based on these data are often lower than expected.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have systematically identified the contributions of both bacteria and viruses to acute respiratory tract infections in adults. Most have been conducted among pneumonia patients in high-income countries [3][4][5][6][7][8], among children [9], or have used limited diagnostic testing [10]; only one meta-analysis has looked at viral etiologies of acute respiratory tract infections in adults across multiple countries [11]. Studies in resource-rich countries may not be applicable to low-and middle-income countries due to differences in pathogen prevalence and variations in risk factors for disease (e.g., hygiene, access to clean water, malnutrition, crowding, HIV prevalence, health care access, vaccination rates, air pollution) among the populations.…”
Section: Introductionmentioning
confidence: 99%